2009
DOI: 10.3748/wjg.15.1119
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and socio-economic factors in relation to Helicobacter pylori re-infection

Abstract: High dietary intake of probiotic bacteria, mainly Lactobacillus, and antioxidants, mainly vitamin C (contained in fruit and vegetables), might decrease the risk of H pylori re-infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Algunos autores refieren que el consumo moderado de alcohol podría estar inversamente asociado a la seroconversión de Hp 19,29 . Sin embargo, se ha considerado, al estudiar la relación de factores como la dieta y el estado socioeconómico, que no existe asociación entre infección por Hp con consumo de alcohol, café y tabaquismo 30 . En este estudio se observó relación entre el consumo de alcohol y la infección por Hp; el riesgo de presentar la infección es mayor en personas consumidoras de alcohol que en aquellas que no lo consumen, con una probabilidad de presentarlo hasta 1.45 veces más, con un intervalo de 1.01 a 2.06.…”
Section: Discussionunclassified
“…Algunos autores refieren que el consumo moderado de alcohol podría estar inversamente asociado a la seroconversión de Hp 19,29 . Sin embargo, se ha considerado, al estudiar la relación de factores como la dieta y el estado socioeconómico, que no existe asociación entre infección por Hp con consumo de alcohol, café y tabaquismo 30 . En este estudio se observó relación entre el consumo de alcohol y la infección por Hp; el riesgo de presentar la infección es mayor en personas consumidoras de alcohol que en aquellas que no lo consumen, con una probabilidad de presentarlo hasta 1.45 veces más, con un intervalo de 1.01 a 2.06.…”
Section: Discussionunclassified
“…204,205 High dietary intake of vitamin C might also decrease the risk of H. pylori re-infection. 206 …”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…This is in line with findings of some previous reports. [1415] New evidence suggested that phytochemical components found in vegetables such as isothiocyanate sulforaphane and glucosinolate can inhibit H. pylori colonization and gastric mucosa inflammation and thus, they may have antibacterial activity against H. pylori . [24] In contrast, some studies reported that H. pylori -positive individuals had significantly higher intake of raw vegetables compared to negative ones which may be contributed intransmission of bacteria through contaminated foods probably due to poor hygiene conditions of study population.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that some dietary factors such as fruits and vegetables may have a protective effect against H. pylori infection likely due to their antioxidants-rich contents. [1415] On the other hand, some reports indicated that diet may increase the susceptibility to H. pylori infection through contamination of foods with H. pylori bacterium. [1617] The relationship of diet-infection is still unclear and providing further evidences to elucidate this association seems to be crucial.…”
Section: Introductionmentioning
confidence: 99%